The work of older people and their informal caregivers in managing an acute health event in a hospital at home or hospital inpatient setting - Makela, P; Stott, D; Godrey, M; Ellis, G; Schiff, R; Sheppard, S (Oxford University Press, 2020)
Background: There is limited understanding of the contribution made by older people and their caregivers to acute healthcare in the home, and how this compares to hospital inpatient healthcare.